2018
DOI: 10.1371/journal.pone.0199474
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the National Tuberculosis Control Program in the post conflict Liberia

Abstract: BackgroundTuberculosis is a major public health problem in Liberia. According to the World Health Organization (WHO), the incidence of tuberculosis in Liberia is significantly increasing from year to year. However, little is known about the performance of the programme and the challenges after the 14 years of civil war which ended in 2003.The purpose of the study was to evaluate the performance of the TB programme of Liberia.MethodsThe study utilised mixed research design; both quantitative and qualitative met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 21 publications
0
25
0
2
Order By: Relevance
“…Our findings as well as the findings from similar study indicated that HIV testing among TB patients, which relies on the finger-prick test which was not recommended during an Ebola outbreak, decreased, leading to a reduction in the number of individuals diagnosed with HIV [13]. Shortcomings in ascertaining HIV status affected the uptake of both CPT needed for preventing opportunistic disease and ART [5]. Our findings were similar to the study conducted by Alyssa et al [13].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our findings as well as the findings from similar study indicated that HIV testing among TB patients, which relies on the finger-prick test which was not recommended during an Ebola outbreak, decreased, leading to a reduction in the number of individuals diagnosed with HIV [13]. Shortcomings in ascertaining HIV status affected the uptake of both CPT needed for preventing opportunistic disease and ART [5]. Our findings were similar to the study conducted by Alyssa et al [13].…”
Section: Discussionmentioning
confidence: 60%
“…In Liberia, the treatment success rate was 76% in 2009 [4, 5]. This figure was by far less than the national and global targets of 85% set by the Stop TB strategy of WHO [6].…”
Section: Introductionmentioning
confidence: 99%
“…This was far lower than the Global WHO End TB targets and strategies aimed at a 95% reduction in TB deaths and a 90% reduction in the TB incidence rate [16]. Even the TB detection rate of above 70% of the 2015 millennium development goal targets were not met [4, 6, 16]. The authors of this study; Desta et al [4], stated the reason for not meeting the target in their previously published paper: “The decline in 2014 and 2015 was attributed to high rate of loss to follow-up as result of the EVD outbreak.” Even though Sierra Leone was among the three EVD-affected countries in West Africa, the case detection rate was 60% and the TB treatment success rate was 86.7% in 2015 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Each slide carried 10 points, and the total maximum score was 100 (for 10 slides). A performance score of less than 90 (90%) was considered to be unacceptable by the WHO TB EQA standard [4, 8, 9]. In addition to this, on-site assessment of 107 functional TB microscopy laboratories was included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation